Modeling Contaminant Microbes in Rivers During Both Baseflow and Stormflow. Issue 8 (18th April 2022) - Drummond, J. D.; Aquino, T.; Davies‐Colley, R. J.; Stott, R.; Krause, S.
Abstract: Rivers transport contaminant microorganisms (including fecal indicator bacteria and human pathogens) long distances downstream of diffuse and point sources, posing a human health risk. We present a mobile‐immobile model that incorporates transport as well as immobilization and remobilization of contaminant microbes and other fine particles during baseflow and stormflow. During baseflow conditions, hyporheic exchange flow causes particles to accumulate in streambed sediments. Remobilization of stored particles from streambed sediments occurs slowly during baseflow via hyporheic exchange flow, while remobilization is vastly increased during stormflow. Model predictions are compared to observations over a range of artificial and natural flood events in the dairy contaminated Topehaehae Stream, New Zealand. The model outputs closely matched timing and magnitude of E. coli and turbidity observations through multiple high‐flow events. By accounting for both state‐of‐flow and hyporheic exchange processes, the model provides a valuable framework for predicting particle and contaminant microbe behavior in streams. Plain Language Summary: Contaminant microorganisms, including the bacterial indicator E. coli, and various disease‐causing bacteria, viruses, and pathogens, are highly episodic in rivers—with typically low‐contaminant microorganism concentrations during low flows that are 100− fold or more increased during storms. At low flow, microbes and other fine particles tend to accumulate steadily in near‐surface streambed sediments (the "hyporheic zone"), but these stores are remobilized by accelerating currents as flow increases. We developed a numerical model framework to represent exchanges of particles and microbes between water and the streambed sediments under variable states of flow—including the deeper streambed as well as the hyporheic zone. Our model was able to capture microbial behavior measured over both a natural storm event and a series of three artificial floods (without any wash‐in from land) in the dairy‐contaminated Topehaehae Stream, New Zealand. Our modeling approach provides a useful framework for predicting microbial behavior and associated hazards within rivers and downstream waters. Key Points: Remobilization of microbes is dependent on both their antecedent accumulation in streambed sediments and the magnitude of stream flow Storm events mobilize microbes from streambed stores that are replenished during the falling limb of the storm hydrograph and baseflow Our particle tracking mobile‐immobile model captures exchanges between the surface water, the hyporheic zone and deeper streambed